The Use of Two Culturing Methods in Parallel Reveals a High Prevalence and Diversity of Arcobacter spp. in a Wastewater Treatment Plant. (17th November 2016) - Levican, Arturo; Collado, Luis; Figueras, Maria José
Abstract : The genus Arcobacter includes species considered emerging food and waterborne pathogens. Despite Arcobacter has been linked to the presence of faecal pollution, few studies have investigated its prevalence in wastewater, and the only isolated species were Arcobacter butzleri and Arcobacter cryaerophilus . This study aimed to establish the prevalence of Arcobacter spp. at a WWTP using in parallel two culturing methods (direct plating and culturing after enrichment) and a direct detection by m-PCR. In addition, the genetic diversity of the isolates was established using the ERIC-PCR genotyping method. Most of the wastewater samples (96.7%) were positive for Arcobacter and a high genetic diversity was observed among the 651 investigated isolates that belonged to 424 different ERIC genotypes. However, only few strains persisted at different dates or sampling points. The use of direct plating in parallel with culturing after enrichment allowed recovering the species A. butzleri, A. cryaerophilus, Arcobacter thereius, Arcobacter defluvii, Arcobacter skirrowii, Arcobacter ellisii, Arcobacter cloacae, and Arcobacter nitrofigilis, most of them isolated for the first time from wastewater. The predominant species was A. butzleri, however, by direct plating predominated A. cryaerophilus . Therefore, the overall predominance of A. butzleri was a bias associated with the use of enrichment.